Prag, Holz und die Johanniter in der zweiten Hälfte des 14. Jahrhunderts - Jan, Libor (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)
Prague, wood and the Hospitaller in the second half of the 14th century This article emphasizes the role of wood for many areas of human activity in the Middle Ages. Of course, this is also connected with the timber trade and its transport, for which waterways were primarily used. On the basis of two sources, namely a visitation of the Hospitaller commanderies in the Prague archdiocese from 1373 and a torso of the accounts of the same religious house from the 1480s, the author shows the mechanisms of these activities, which were carried out under the direction of the Prague commanderies. For the Prague Hospitallers, the enclave to the south upstream of the Vltava River was important, where they owned several villages as well as adjacent forests. The centre was the farmstead (curia) in Varvažov, whose administrator was one of the knightly members of the Prague Convent. The transport by boat of the timber assembled into rafts was carried out mainly by the serfs from Varvažov, Nevězice and Zbonín, who were burdened with only small financial contributions. With the price of one raft between costing 12‒32 Prague groats, the Order was able to earn almost 100 three-scores (i.e. 6,000 groats) annually, which was divided in half between the Prague Commander and the administrator from Varvažov. However, the order’s witnesses, Commander Pesslin and Prior Nicholas, did not mention the timber trade at all in their visitations.